Strength and Expansion and Deformation Characteristics of Modified Expansive Soil by Octadecylamine - Jun-Hua Wu; Wei-Chao Ao; Mao-Sheng Wang; Jia-Ming Liu; Fang-Yuan Fu (Advances in Civil Engineering)
Octadecylamine was used as a primary water repellent and mixed into the remodeled expansive soil, and modified expansive soils with different water contents and octadecylamine contents were configured. The water repellency level of the modified expansive soil was determined by the drip penetration time method, the corresponding free, unloaded, and loaded swelling rate tests were carried out, and the law of the influence of octadecylamine content and water content on the expansion and deformation of expansive soil was obtained. It can be shown that the modified expansive soil with an octadecylamine content of 0.8% (mass fraction) had an extreme water repellent grade, and the water repellency remained stable. The more the water content and octadecylamine content, the lower the free swelling rate, and the unloaded swelling rate and loaded swelling rate of modified expansive soil tended to be stable. When the octadecylamine content was 0.5% and 0.8%, the free expansion rate was significantly reduced, and the maximum drop was 42%. When the octadecylamine content was increased from 0% to 0.8%, the uncharged expansion stability duration was shortened from 97 h to 47 h, and the expansion rate was reduced from 12.9% to 9.4%. When the mass fraction of octadecylamine was 0.8%, the modified expansive soil with a water content of 20% would decrease its load expansion rate from 2.14% at 50 kPa to 0.01% at 400 kPa. When the load was small, the octadecylamine content and initial water content had a greater impact on the loaded expansion rate; when the load was large, the load became the main factor affecting the loaded expansion rate. Under the same overburden pressure, the more the octadecylamine content was, the lower the soil shear strength was and the more it tended to be stable.